Bars and boxes - Pacheco, Ana Paula (Revista do Instituto de Estudos Brasileiros, 2023)
The Creation section has the objective of publish unpublished texts and materials by writers and/or artists, photographers, designers, as well as unpublished documents found in the USP IEB Archive. “Bars and boxes”, by Ana Paula Pacheco, gathers two tales about the feminine. Pacheco is writer and professor of Literary Theory and Comparative Literature in the Sao Paulo University. “Pedaços de sonho, seguidos de considerações tecidas pelo Urso siberiano” benefits from the studies by Freud (1972), Schnitzler (1987; 2008) and Nastassja Martin (2021). In addition, “Pandora, a barata” freely incorporates the studies by Erwin and Dora Panofsky (2009).